2014
DOI: 10.5539/jas.v6n9p37
|View full text |Cite
|
Sign up to set email alerts
|

Growth Responses of Two Kenaf Varieties (Hibiscus cannabinus L.) Applied by Different Levels of Potassium, Boron and Zinc

Abstract: The aim of this study was to determine the effect of potassium, boron and zinc rates on the growth of kenaf. Seeds of two kenaf varieties namely; FH-952 and 4383 variety were planted on 26 September 2013. Plant growth was determined for both varieties. The growth characteristics which consist of plant height, stem diameter and leaf number were measured every two weeks for five times consecutively. The best result was achieved for both characteristics; stem diameter and leaf number for FH-952 variety when potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
4
4
0
Order By: Relevance
“…Hybrid was flowering after 165 days, while could see the flower on V36 after 195 days of planting. It was in agreement with previous research which concluded that growth parameters were different with kenaf varieties (Salih et al, 2014b). FH-952 variety had the highest stem compared to other varieties were studied.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Hybrid was flowering after 165 days, while could see the flower on V36 after 195 days of planting. It was in agreement with previous research which concluded that growth parameters were different with kenaf varieties (Salih et al, 2014b). FH-952 variety had the highest stem compared to other varieties were studied.…”
Section: Resultssupporting
confidence: 92%
“…Despite that, kenaf V36 had to the smallest stem diameter which was only (18.6 mm). These results strongly supported by (Salih et al, 2014b;Hossain et al, 2011;and Wong et al, 2008). Many factors effected stem diameter such as field management and varieties.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Different levels of potassium fertilizer were apllaied to two varieties of kenaf FH-952 and 4383 that planted in 2013 at Universiti Putra Malaysia (UPM). Growth and yield parameters were improved by adding potassium especially at the rate of 150 kg/ha (Salih et al, 2014a). Additionally, potassium has probable cause in an increasing the amount of crop yield and improving the quality of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Fertilizer application is necessary for high yielding Kenaf. There are many reports published on fertilizer requirement for kenaf production [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In Bangladesh farmers are not well known of better kenaf production technology that hinders the expected production of Kenaf and fibre and seeds are grown conventionally [20].…”
Section: Introductionmentioning
confidence: 99%